2019
DOI: 10.1093/jnci/djz068
|View full text |Cite
|
Sign up to set email alerts
|

Expected Monetary Impact of Oncotype DX Score-Concordant Systemic Breast Cancer Therapy Based on the TAILORx Trial

Abstract: Background TAILORx demonstrated that women with node-negative, hormone receptor-positive, HER2-negative breast cancers and Oncotype DX recurrence scores (RS) of 0–25 had similar 9-year outcomes with endocrine vs chemo-endocrine therapy; evidence for women aged 50 years and younger and RS 16–25 was less clear. We estimated how expected changes in practice following the trial might affect US costs in the initial 12 months of care (initial costs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…A previous SEER-Medicare study indicated that the rate of chemotherapy receipt was 3.7%, 9.5%, and 58.3% in low, intermediate, and high RS of patients aged between 65 and 74 years, respectively [33], which was similar to our results. However, the rate of chemotherapy receipt was still significantly lower than that of young patients.…”
Section: Discussionsupporting
confidence: 92%
“…A previous SEER-Medicare study indicated that the rate of chemotherapy receipt was 3.7%, 9.5%, and 58.3% in low, intermediate, and high RS of patients aged between 65 and 74 years, respectively [33], which was similar to our results. However, the rate of chemotherapy receipt was still significantly lower than that of young patients.…”
Section: Discussionsupporting
confidence: 92%
“…We also assessed the concordance between the two scores according to age: ≤50 years and >50 years. Based on recent findings on the benefits of chemotherapy for patients with a RS midrange score (1125) from TAILORx (23), patients were categorized into chemobenefit and non-chemobenefit groups using different RS ranges for each age subgroup. In patients aged ≤50 years, those with RS 0–15 and RS ≥16 were categorized into non-chemobenefit and chemobenefit groups, respectively, whereas in patients aged >50 years, the RS ranges used for the classification into non-chemobenefit and chemobenefit groups were RS 0–25 and RS ≥26, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the ARR and NNT for a RS ≥26 was 25.0 and 4.0, respectively (24). A recent study showed that tailored therapy based on Oncotype DX results could result in a net cost increase in initial care of American breast cancer if women aged ≤50 years with tumors with RS of 16–25 all chose to receive chemotherapy (25).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the reported analysis suggests that data for evaluating the potentially most efficient two-step testing strategy is missing. 47 , 48 Mariotto and colleagues 49 showed that application of the 21-RS risk to decide whether or not to provide chemotherapy would produce savings in the actual US real clinical practice. Another analysis using the same data indicates that savings would be much larger if testing would be performed according to a two-step strategy.…”
Section: Resultsmentioning
confidence: 99%